Anisotropic mechanical properties and cushioning effectiveness of spruce subjected to different direction loading - Zexiong Zhang; Weizhou Zhong; Jiaxing Li; Jingrun Luo (Materials Research Express)
The arrayed microstructure of wood produced during growth results in anisotropic mechanical behavior at the macroscopic level. In order to assess the cushioning effectiveness of spruce, the microstructural models with regular hexagonal array cells along axial, tangential, radial and 15°, 30°, 45°, 60°, 75° relative to the axial direction in tangential section were established. The mechanical responses of spruce along different loading directions were given by numerical simulations and experiments. The anisotropic mechanical properties and cushioning effectiveness of spruce were analyzed comparatively. Three prediction formulas were proposed to investigate the mechanical properties of spruce along different loading directions. The deformation characteristics, energy dissipation pattern and failure mechanism along different loading directions were given, and the influence of spruce microstructure on anisotropic mechanical behaviour with different direction were discussed.